STUDENT DEMONSTRATION IN NATIONAL SECURITY PERSPECTIVES (CASE STUDY OF STUDENT DEMONSTRATION BY BADAN EKSEKUTIF MAHASISWA SELURUH INDONESIA OR BEM SI ON APRIL 11, 2022) - Nababan, Kristina Roseven (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2022)
National security is a battle against threats from both within and outside the country. It is the same with the recent demonstration by Badan Eksekutif Mahasiswa Seluruh Indonesia (BEM SI) or Student Executive Board throughout Indonesia. The demonstration can be both an opportunity and a challenge in the development of national security. This study will provide insight into how the BEM SI demonstration on April 11, 2022, which is expected to bring demands on the issue of postponing the 2024 election and a three-term term for President Jokowi, will affect national security. This study employs descriptive quantitative research, with data collected by a survey of 200 students throughout Indonesia. The findings of this study indicate that the BEM SI demonstration was on April 11, 2022. Social media plays a role in influencing student behavior to take action. As a result, students should evaluate demonstration practices and reclaim their role as agents of change.Â